KAJIAN LITERATUR TENTANG KONSEP DASAR PEMBELAJARAN DALAM PENGEMBANGAN STRATEGI PEMBELAJARAN - Setiani, Anggun; Siti Nur Azizah; Baihaqi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning is a process of interaction between teachers, students, and learning resources aimed at creating planned changes in knowledge, skills, and attitudes. This literature review aims to analyze the basic concepts of learning to help develop effective learning strategies. The method used is a literature study, examining various scientific sources on learning and learning strategies. The results of the study indicate that learning has several main components: teachers and students, learning objectives, materials, methods, media, and assessment. Learning is also based on principles such as motivation, student engagement, individual differences, and direct student involvement. A learning strategy is a systematic plan that includes the selection of approaches, methods, techniques, media, and learning resources to achieve learning objectives effectively and efficiently. Examples of frequently used strategies include expository, inquiry, and cooperative learning. The choice of strategy is influenced by internal student factors (physical condition, intelligence, interests, talents) and external factors (family, school, and community environments). This study confirms that a deep understanding of basic learning concepts is essential for teachers to design strategies that are appropriate to student characteristics and the demands of 21st-century education. With the right strategies, students' motivation, engagement, critical thinking skills, and learning outcomes can improve.